Anthology as a form of systematisation and popularisation of American literature about the World War I - Tratsiak, Zoya I. (Journal of the Belarusian State University. Philology, 2025)
Anthologies «Armageddon. The World War in literature», «Men at war», «World War I in American fiction: an anthology of short stories» published in the USA throughout the century after the end of the World War I are studied. Their role in the formation of the national literary canon (including the works by J. Dos Passos, W. Faulkner, E. Hemingway) and popularisation of T. Boyd’s, E. E. Cummings’s, K. A. Porter’s, L. Stallings’s, C. Sandburg’s, J. B. Wharton’s, B. Schindel’s legacy is highlighted. The compilers’ approaches to the systematisation of stylistically and thematically diverse literary, artistic and documentary material are studied. The role of the reader is outlined. Analysing the works proposed, the reader notices that independent literary and artistic units begin to function as a complementary unity, endowed with a highly suggestive potential, where special thematic dominants, allusions, symbols are noticed.
Keywords: World War I; American literature; war literature; anthology; memorialisation; complementarity; suggestiveness; literary canon